2013
DOI: 10.2500/ajra.2013.27.3864
|View full text |Cite
|
Sign up to set email alerts
|

Mometasone Furoate Nasal Spray plus Oxymetazoline Nasal Spray: Short-term Efficacy and Safety in Seasonal Allergic Rhinitis

Abstract: Combining MFNS with OXY relieves SAR symptoms, including congestion, with faster onset of action than MFNS q.d. and better sustained efficacy than OXY b.i.d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 20 publications
1
51
0
3
Order By: Relevance
“…Four RCTs were removed after the full text screening. At the end, 6 RCTs were included . The RCTs retrieval and selection process including reasons for exclusion are listed in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four RCTs were removed after the full text screening. At the end, 6 RCTs were included . The RCTs retrieval and selection process including reasons for exclusion are listed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 1071 participants with mean age of 36.7 years (reported in 5 trials) and 36.0% were male (reported in 5 trials). Three RCTs included patients with AR only while the other 3 RCTs included mixed population of AR and NAR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OXY has been demonstrated to have various antioxidant and anti-inflammatory properties in addition to its potent decongestive effect2425. Previous studies have demonstrated that the concomitant administration of MF and OXY may provide better improvements in AR patients, especially those with nasal congestion symptom262728293031. Therefore, the initial thought of this study was that this decongestant would improve airflow and nasal volume and that MF may act on the turbinate and AH tissue more fully and quickly.…”
Section: Discussionmentioning
confidence: 98%